2018
DOI: 10.1021/acs.jmedchem.7b01728
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Fragment-Based Design Identifies Subfamily B1 Metallo-β-lactamase Inhibitors

Abstract: Zinc ion-dependent β-lactamases (MBLs) catalyze the hydrolysis of almost all β-lactam antibiotics and resist the action of clinically available β-lactamase inhibitors. We report how application of in silico fragment-based molecular design employing thiol-mediated metal anchorage leads to potent MBL inhibitors. The new inhibitors manifest potent inhibition of clinically important B1 subfamily MBLs, including the widespread NDM-1, IMP-1, and VIM-2 enzymes; with lower potency, some of them also inhibit clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Representative inhibitors of NDM-1 [28][29][30][31][32][33][34][35][36]. ChemMedChem 2019, 14,1271 -1282 www.chemmedchem.org 2019 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim 3, 5, 6,a nd 8 are summarized in Scheme 2.…”
mentioning
confidence: 99%
“…Representative inhibitors of NDM-1 [28][29][30][31][32][33][34][35][36]. ChemMedChem 2019, 14,1271 -1282 www.chemmedchem.org 2019 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim 3, 5, 6,a nd 8 are summarized in Scheme 2.…”
mentioning
confidence: 99%
“…135 Other studies employed mercaptoacetamide thioethers containing acetate 136 and azolyl ring [137][138][139][140] substituents. The diverse library of thiolcontaining MBL-inhibitors also include thiomethylbenzoic acids, 141 bisthiazolidines, 142,143 rhodanines and its related thioenolates, [144][145][146][147] cysteine-containing oligopeptides, 148,149 phosphonate and tetrazole bioisosters of mercaptoacids 150 and thiones. [151][152][153][154] Finally, it should be added that although thiols are among the most potent and broad-spectrum inhibitors of MBLs, their tendency to rapidly oxidize to disulfides poses a serious challenge to further clinical developments.…”
Section: Recent Advances In the Development Of Mbl Inhibitorsmentioning
confidence: 99%
“…However, these inhibitors display low inhibitory activity against other members of VIM or other B1 enzymes. In the next study, Schofield group identified several thiol MBL inhibitors based on the design of silico fragment, which has significant inhibitory effects on NDM‐1, VIM‐2, and IMP‐1 (Cain et al., ). Interestingly, the crystal structure of compound 1 (Figure .22) and VIM‐1 showed that it acts as a metal‐binding ligand, replacing the “hydrolyzed” hydroxide ion bridging the two metal ions.…”
Section: Progress In Designing Metallo‐β‐lactamase Inhibitorsmentioning
confidence: 99%
“…Cain report an application of silico fragment‐based molecular design employing thiol‐mediated metal anchorage leads to potent MBL inhibitors. The new inhibitors are effective in inhibiting the important B1 subfamily MBLs (NDM‐1, IMP‐1, and VIM‐2), while some of them also have a lower inhibitory effect on clinically relevant class A and class D serine‐β‐lactamase (Cain et al., ).…”
Section: Discovery and Screening Approaches For Mbl Inhibitorsmentioning
confidence: 99%